Annals of the Rheumatic Diseases collection on pregnancy 2018–2023: observational data-driven knowledge - Duhig, Kate; Hyrich, Kimme L (Annals of the rheumatic diseases, 2024)
Pregnancy can be an exciting time but for those living with rheumatic musculoskeletal diseases (RMDs), it can also be a time fraught with concern, including what effect pregnancy will have on the underlying RMD and what effect the RMD may have on the pregnancy and the baby, including the effects of medications. Generating an evidence base in pregnancy is challenging. Few interventional trials of medications in RMD pregnancies have ever been conducted, often for concerns of safety for both the mother and the child. Therefore, observational research remains important for informing clinical practice and helping women with RMDs make decisions regarding their health preconception and during pregnancy. The Annals of the Rheumatic Diseases (ARD) continues to publish important research on pregnancy in RMDs to increase the evidence base on this subject. Here we present an overview of papers published on this topic between January 2018 and December 2023. Our focus includes papers on pregnancy and RMD outcome, the effects of drug exposure, fetal outcomes as well as fertility.